EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN BERBICARA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS IV SDN 69 GALESONG 1 - Sarmila; Ainun Sahirah Ulia, Nur qalbi; Arifuddin, Desy Ayu Andhira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of the Jigsaw cooperative learning model on the speaking ability of fourth-grade students at SDN 69 Galesong 1. The research problem was the low speaking ability of students, with only 20% achieving the KKM of 75 in the initial observation. The methodology used was Classroom Action Research (CAR) conducted in two cycles. The subject of the research was 25 students. Data was collected through speaking ability tests and observation. The results showed a significant improvement from Cycle 1 to Cycle 2. In Cycle 1, only 20% of students passed the KKM, while in Cycle 2, the rate increased to 100%. The class average score also rose significantly from 65.6 to 84.2. This proves that the Jigsaw cooperative learning model is highly effective in improving students' speaking ability, promoting fluency, clarity, and confidence through active group collaboration.